Assessment of stress in effect to pyrethroid insecticides, Î»-cyhalothrin and cypermethrin, in a freshwater fish, Channa punctatus (BLOCH) - Kumar, A.; Sharma, B.; Pandey, R. S. (Cellular and Molecular Biology, 2012)
The present study was planned to see the changes in the levels of different biochemical stress markers such as the level of lipid peroxidation and the specific activities of lactate dehydrogenase (LDH), acid and alkaline phosphatases in different organs such as brain, liver, kidney, gills and muscle of a freshwater muddy fish, Channa punctatus in effect to pyrethroid insecticides, cypermethrin and Î»-cyhalothrin treated for 96 h. The results showed significant increase in the levels of lipid peroxidation as well as the activities of LDH, acid and alkaline phosphatases in a dose dependent manner. The remarkable increase in the levels of these stress biomarkers indicates strong stress inducing potential of these insecticides in fishes. The importance of the current study lies in indicating the potential risk of muddy freshwater fishes due to strong soil binding property of pyrethroids along with their slow metabolism in fishes as compared to that of mammals.